Manfaat Pemidanaan Dalam Penanggulangan Tindak Pidana Narkotika - Milton Lilipory; John Dirk Pasalbessy; Yanti Amelia Lewerissa (TATOHI: Jurnal Ilmu Hukum, 2023)
Introduction: The criminalization of narcotics offenders is often subject to heavy penalties, but for potential perpetrators there is no deterrent effect, even recidivist or repeat offenders never feel deterred. Therefore, it is necessary to find alternative solutions to narcotics abuse more effectively so that it can have a deterrent effect on both the perpetrators and potential perpetrators.Purposes of the Research: The purpose of this study is to analyze and explain the meaning and purpose of imposing criminal sanctions against narcotics abuse, so that the perpetrators or potential perpetrators become deterrent, as well as to discuss the purpose of imposing heavy penalties for perpetrators of drug abuse in terms of the theories of the purpose of punishment that have been adopted in the development of criminal law. Methods of the Research: The method used in this study is a normative juridical method with a statutory approach, a conceptual approach and a case approach. The legal materials used are library law materials. Thus, the legal materials studied and analyzed in normative legal research consist of primary legal materials, such as legislation, secondary legal materials in the form of legal literature, consisting of books, scientific journals, legal documents and so on, as well as legal materials. tertiary in the form of legal dictionaries, encyclopedias and so on.Results of the Research: Based on the results of the study, it is shown that the imposition of serious crimes against narcotics traffickers is not always able to solve the problem of lawbreakers, both seen from the theories of classical criminal law, modern criminal law and new classical criminal law. This is reasonable because the prevention of crime lies not only in the model or duration of the punishment given and served later, but on the criminal system adopted in a country that it adheres to. The problem of whether or not a person is deterred is not determined by how much sanctions are given, because the provision of sanctions and whether or not a person is deterred depends on the attitude of people and society towards the crime he feels.